"Precarious upgrading" in electronics global production networks in Central and Eastern Europe: The cases of Hungary and Romania - Leonhard Plank; Cornelia Staritz (Austrian Foundation for Development Research (ÖFSE), 2013)
The electronics manufacturing sector has played a prominent role in export-oriented development strategies, as participation in this high-tech industry promises access to new technology, high skilled jobs and a fast-growing market. Against this background, many governments in Central and Eastern Europe (CEE) have sought to attract investment in this sector, where foreign firms became the key actors in reshaping after 1989 and where integrating into global production networks (GPNs) was widely embraced as a means to modernize and upgrade local industries. We assess to what extent the potential benefits arising from integrating into electronics GPNs have materialized in Hungary, an established player and the most important electronics exporting country in the region, and Romania, a newcomer country in electronics manufacturing. To analyse these questions, we look at the organizational and geographical configuration of the electronics sector and examine the impact integration into these networks has had on local firms and workers and to what extent this integration has led to economic and social upgrading. With regard to economic upgrading processes, we suggest that the upgrading concept needs to pay more attention to the 'reach' of economic upgrading. This is particularly important when integration into GPNs takes place via foreign direct investment (FDI), where economic upgrading processes may be focused on transnational corporations (TNCs) with limited spillovers to local firms. The social upgrading trajectory is influenced importantly by global industry dynamics, for example high flexibility pressures and the tiered nature of the workforce in electronics GPNs, and countries' specific institutional and regulatory contexts.
Keywords: 330; global production networks; electronics sector; foreign direct investment; economic upgrading; social upgrading; Central and Eastern Europe; Hungary; Romania; Elektronisches Produkt; Internationale Arbeitsteilung; Auslandsinvestition; Ungarn; Rumänien; Osteuropa